Role of lean, agile, resilient, green, and sustainable paradigm in supplier selection - Harshad Sonar; Angappa Gunasekaran; Swati Agrawal; Matthew Roy (Cleaner Logistics and Supply Chain)
During the new COVID-19 outbreak, companies are looking to sourcing leaders to assist them diversify their supply base and prepare for a number of situations. In recent days, the role of emerging paradigms, including lean, agile, resilient, green, and sustainability (LARGS) in highly competitive supply chains, has been gaining momentum. However, there is no research on the LARGS paradigm for sustainable supplier selection in the literature. The aim of this paper is to identify important criteria for supplier selection in the LARGS paradigm and to develop the hierarchical relationship between the criteria. This research has identified 22 key criteria for supplier selection in the LARGS paradigm. Data were collected from 12 experts and analysed by interpretive structural modeling (ISM). From the ISM model, it is observed that geographic location is placed at the bottom of the hierarchy, showing high driving power and the most important criteria while selecting any supplier. Lead time also indicates high driving power and organizations must focus on the suppliers' lead time to improve product performance and introduce new products faster into the markets. The findings will help the practitioners and policymakers to formulate supply chain robustness and resilience strategies to diminish supply chain risks imposed by the COVID-19 pandemic. The presented model can be assessed as a strategic tool to select a supplier who considers lean, agile, resilient, green, and sustainable criteria simultaneously to increase supply chain efficiency and effectiveness. The study is first of its kind to identify supplier selection criteria in LARGS paradigm and develop hierarchical relationships between them using ISM approach.